2021
DOI: 10.1088/1742-5468/abda27
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and topological study of the Kosterlitz–Thouless phase transition in the XY model in two dimensions

Abstract: Phase transitions do not necessarily correspond to a symmetry-breaking phenomenon. This is the case of the Kosterlitz–Thouless (KT) phase transition in a two-dimensional classical XY model, a typical example of a transition stemming from a deeper phenomenon than a symmetry-breaking. Actually, the KT transition is a paradigmatic example of the successful application of topological concepts to the study of phase transition phenomena in the absence of an order parameter. Topology conceptually enters through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…To the contrary, the set of uncoupled harmonic oscillators is integrable, however, each single harmonic oscillator is ergodic in its own two-dimensional phase space, and, since all the oscillators have the same frequency, so that they are interchangeable, and the initial conditions are random, also this systems behaves as if it was ergodic, as the stability of the results of the computation of the geometric observables has been checked by changing the initial conditions. In fact, given an observable, Φ, defined on the phase space, the microcanonical averages can be measured along the dynamics as follows [23,34]:…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the contrary, the set of uncoupled harmonic oscillators is integrable, however, each single harmonic oscillator is ergodic in its own two-dimensional phase space, and, since all the oscillators have the same frequency, so that they are interchangeable, and the initial conditions are random, also this systems behaves as if it was ergodic, as the stability of the results of the computation of the geometric observables has been checked by changing the initial conditions. In fact, given an observable, Φ, defined on the phase space, the microcanonical averages can be measured along the dynamics as follows [23,34]:…”
Section: Numerical Resultsmentioning
confidence: 99%
“…On the other hand, the Landau theory, which relates phase transitions with the symmetry-breaking phenomenon, is not an all-encompassing theory because there are many systems undergoing phase transitions in the absence of an order parameter, and thus in the absence of symmetry-breaking [22,23]. Therefore, looking for generalizations of the existing theories is a well motivated and timely purpose.…”
Section: Introductionmentioning
confidence: 99%
“…That is, a continuous change in the configuration space geometry brought about a divergence in the mixing time, and while such events are often accompanied by topological changes they are not always. The significance of the configuration space geometry is supported by a recent study of the topological and geometric properties of the two-dimensional XY model by Bel-Hadj-Aissa et al [13]; they computed the mean geometric curvature of the equipotential energy level sets and observed that the location of the phase transition could be inferred from the level set curvatures.…”
Section: Introductionmentioning
confidence: 93%
“…We evaluated the geometric observables in Eq. ( 9) exploiting the ergodic hypothesis, that is, we converted the microcanonical averages into time averages [18,20]. More precisely, given a generic phase-space-valued function, f : Λ → R, we have…”
Section: Expression Of the Geometric Observablesmentioning
confidence: 99%